1999
DOI: 10.1088/0963-0252/8/1/019
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the role of ultraviolet radiation of the non-equilibrium plasma in the dynamics of the microwave discharge in molecular nitrogen

Abstract: A self-consistent plasmachemical model describing the dynamics of the non-equilibrium microwave discharge in molecular nitrogen with consideration for kinetic, photochemical and electrodynamic phenomena is proposed. The photochemical block of the model accounts for the processes of photoexcitation and photoionization of nitrogen molecules in the ground and excited electronic states. Radiative emittance of the discharge plasma is conditioned by the processes of photorecombination of electrons and positive ions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 29 publications
1
53
0
Order By: Relevance
“…For example, about 2 eV must go to a gas heating in the quenching process of N2(a 1 Пg) state with the excitation energy of 8.6 eV. This assumption [3] is inconsistent with the experimental results [14][15][16], where the authors showed that the energy transfer between electronically excited N2 molecules occur with minimal energy release converted to the translational degrees of freedom of reaction products. Therefore the problem of fast gas heating in nitrogen discharge plasma still remains open.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…For example, about 2 eV must go to a gas heating in the quenching process of N2(a 1 Пg) state with the excitation energy of 8.6 eV. This assumption [3] is inconsistent with the experimental results [14][15][16], where the authors showed that the energy transfer between electronically excited N2 molecules occur with minimal energy release converted to the translational degrees of freedom of reaction products. Therefore the problem of fast gas heating in nitrogen discharge plasma still remains open.…”
Section: Introductionmentioning
confidence: 92%
“…lectronically excited N2(A 3 Σ u + ,v) molecules play an important role in gas discharge kinetics in nitrogen and nitrogen-oxygen mixtures [1][2][3][4][5][6][7][8]. In mixtures with a small fraction of oxygen a considerable part of the discharge energy, spent on excitation of electronic degrees of freedom, accumulates in N2(A 3 Σ u + ) state.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations